Optimization of Blast Furnace Productivity Coupled with CO2 Emissions Reduction. Issue 1 (19th June 2013) - Cavaliere, Pasquale; Perrone, Angelo
Abstract Blast furnace represents the dominant hot metal making production process worldwide and one of the main energy consuming processes. Modern research in the field focuses on the increase in plant productivity through energy saving and on the reduction of greenhouse gas emissions compatible with legal limits. Productivity is governed mainly by relevant input parameters such as materials rates, materials properties, and operating conditions. All the dominant input parameters and their variations have been analyzed in the present study and they have been optimized in order to increase plant productivity and reduce the greenhouse gas emissions. The raw materials quality analyses was largely taken into account especially with regard to sinter and coke quality. The reducibility of raw materials was demonstrated to largely influence plant efficiency. The study suggests new solutions in all processing parameters in order to improve plant productivity and to reduce the dangerous emissions.